Factors influencing the repayment patterns of nonbank financial institution borrowers / Chong Fen Nee ... [et al.] - Chong, Fen Nee; Morni, Fareiny; Suhaimi, Rosita (2010)
This study investigates the factors influencing repayment performance of non-bank financial intemediaries borrowers in Kuching. A total of sixty queationnaires collected during the study period were used for the analysis. Findings showed that 45% of the respondents pay their credit obligations on time while the remaining take between one to six months to settle their monthly arrears. When the cross-tabulation analysis was used to identify the common demographic characteristics of the defaulters, it was found that majority of this group are male, married, has a lower education attaintment and self-employed.